Life Skills Development Training: Adaptation to New Habits and First Aid of Emergency on SLB Bhakti Pertiwi - Irawan Danismaya; Amir Hamzah; Ria Andriani; Erna Safariyah (STIKep PPNI Jawa Barat, 2021)
Aims : People with disabilities are one of the groups that are vulnerable to contracting COVID-19. They have different self-isolation techniques from non-disabled people. So, it requires adjusting the needs and conditions of different disabilities. This effort also requires support from the surrounding, including schools. SLB Bhakti Pertiwi is one of the special schools located in Kecamatan Kadudampit, Kabupaten Sukabumi. The SLB has 34 students and 11 teachers. When other schools carry out online learning during the pandemic of COVID-19, SLB had its own obstacles to adapt because students with disabilities had difficulties following. To overcome this obstacle, the teacher visited each student’s home. However, this situation put the teachers or students at risk. To continue the learning process, efforts need to be made to help students and teachers adapt to new habits. In addition, teachers need to have first aid skills because persons with disabilities have several conditions that require appropriate and immediately treatment. As the special group community, SLB students become targets in this community service. This community service aims to develop basic skills in adapting to new habits as an effort to prevent COVID-19 and also handle emergencies. Design : This community service focus on life skills development training: adaptation to new habits and first aid of emergency on SLB Bhakti Pertiwi students and teachers. Methods : The methods used are counseling, simulation, watching video and fun games. Counseling and simulation are carried out on teachers in developing first aid skills in emergencies, while students are approached by watching videos and doing fun games. Results : The results showed that 80% students have started be able to simulate how to wash hands, wear masks and keep a distance. The teachers are able to re-simulate the first aid steps if a student has a seizure, drowns or experiences external bleeding due to a fall. However, not all students participated in this activity due to poor health conditions. Conclusions : Community service activities in the form of Life Skills Development Training: Adaptation of New Habits and Emergency First Aid have been carried out well within 8 meeting periods. This activity also received a good response from students and teachers. Students and teachers seemed enthusiastic in participating in this activity